THE YOUTH IN RUSSIA: INEQUALITIES AND LIVING CHOICES - E. I. Kuzmina (Vestnik MGIMO-Universiteta)
The paper analyzes the problems of social inequality and life chances of modern Russian youth. Theoretical grounds of the research are the classical and the contemporary social theories concerning social inequality (Parsons, Weber, Sorokin, Warner). The traditional and new forms of inequality are discussed in the paper. The results of the author’s online survey are presented. The aim of the survey is to find out the actual social inequalities which draw a distinction between Moscow youngsters.Particular attention has been given to the determinants of social inequality. The results of the survey show that among the priority ones there are the five major determinants:– the first one is the material status;– the second place goes to temporal factor. Spare time for communication with friends, self-education, hobbies and leisure has become not easily available for many young people;– the third determinant is the place of living and living conditions: the comfort and prestige of city district, its safety and infrastructure;– the fourth place is taken by mental outfit and social capital, in other words, by the body of knowledge and skills which is in demand on the labour market;– the fifth factor is the power, the ability to influence other people (relatives, friends, colleagues, government)We have found out that along with the traditional inequalities the new form of inequality – the temporalinequality – is becoming more and more significant for the Russian youth.